Diagnóstico de Leptospira spp. en cerdos destinados a faenamiento en el matadero municipal del cantón Portoviejo - Giler Zambrano, Gema María (2020)
In order to diagnose the seroprevalence of Leptospira in pigs destined for slaughter, coming from farms in various cantons of the province of Manabí. It was developed in the municipal slaughterhouse of Portoviejo canton. 201 samples were collected from slaughtered pig kidneys, to determine the presence of histopathological lesions, PCR analysis (Real Time), and blood extraction to obtain blood serum and its subsequent analysis of microagglutination-lysis (MAT) for seven serotypes from Leptospira. In addition to a survey of personnel who work to determine risk factors. The results obtained according to the seroprevalence at the slaughterhouse level was 24.37% against Leptospira spp. analyzed by microagglutination-lysis, where Portoviejo canton had an average seroprevalence of 6.97%. The serovars with the highest titers were: Leptospira canicola (20.37%) and Leptospira tarassovi (11.11%). Among the histopathological lesions (tubular nephritis), a significant difference was found for the L. Tarassovi serovar. While the L. icterohemorragiae serovar was present in the Glomerulonefrits (p≤0.05); both related to the presence of pathogenic Leptospira. The risk factors found were: presence of animals (rats, cats and dogs) and absence of safety regulations in the personnel. It is concluded that Leptospira is a disease present with the same occurrence in all diagnosed animals and with the same presence in all provenances in the cantons evaluated.